Effects of STN-DBS on cognition and mood in young-onset Parkinson’s disease: a two-year follow-up - Hong, Jun; Xie, Huimin; Chen, Yuhua; Liu, Di; Wang, Tianyu; Xiong, Kun; Mao, Zhiqi (Frontiers in Aging Neuroscience, 2024)
Background: The effects of subthalamic nucleus deep brain stimulation (STN-DBS) on the cognition and mood of patients with PD are still not uniformly concluded, and young-onset Parkinson's disease (YOPD) is even less explored. Objective: To observe the effectiveness of STN-DBS on the cognition and mood of YOPD patients. Methods: A total of 27 subjects, with a mean age at onset of 39.48 ± 6.24 and age at surgery for STN-DBS of 48.44 ± 4.85, were followed up preoperatively and for 2 years postoperatively. Using the Unified Parkinson disease rating scale (UPDRS), H&Y(Hoehn and Yahr stage), 39-Item Parkinson's Disease Questionnaire (PDQ-39), Mini-mental state examination (MMSE), Montreal Cognitive Assessment (MoCA), Hamilton depression scale (HAMD), Hamilton anxiety scale (HAMA) to assess motor, cognition, and mood. Results: At the 2-year follow-up after STN-DBS, YOPD patients showed significant improvements in motor and quality of life (UPDRS III: p < 0.001, PDQ-39: p < 0.001); overall cognition was not significantly different from preoperative (MMSE: p = 0.275, MoCA: p = 0.913), although language function was significantly impaired compared to preoperative (MMSE: p = 0.004, MoCA: p = 0.009); depression and anxiety symptoms also improved significantly (HAMD: p < 0.001, HAMA: p < 0.001) and the depression score correlated significantly with motor (preoperative: r = 0.493, p = 0.009), disease duration (preoperative: r = 0.519, p = 0.006; postoperative: r = 0.406, P = 0.036) and H&Y (preoperative: r = 0.430, p = 0.025; postoperative: r = 0.387, p = 0.046); total anxiety scores were also significantly correlated with motor (preoperative: r = 0.553, p = 0.003; postoperative: r = 0.444, p = 0.020), disease duration (preoperative: r = 0.417, p = 0.031), PDQ-39 (preoperative: r = 0.464, p = 0.015) and H&Y (preoperative: r = 0.440, p = 0.022; postoperative: r = 0.526, p = 0.005). Conclusions: STN-DBS is a safe and effective treatment for YOPD. The mood improved significantly, and overall cognition was not impaired, were only verbal fluency decreased but did not affect the improvement in quality of life. Key Words: Parkinson’s disease; deep brain stimulation; Cognition; Verbal fluency; Mood